A case of multifactorial dementia - Viveiros, Maria João Albuquerque da Silva (2021)
Introduction: Dementia may present with deterioration of one or several cognitive domains, characterized by impact and maladaptation in the activities of daily living. The presentation of this clinical case is justified by the growing incidence of this diagnosis and the importance of the timely recognition of reversible causal factors for it, allowing for a targeted treatment and the minimization of complications. Case Description: Single, 70-year-old man, former smoker, with a history of alcoholism and sexual risk behavior. He was brought to the consultation by his daughter because of a four-year history of behavioral change, with episodes of hetero-aggressivity, incoherent speech, self-neglect, progressive loss of autonomy, and motor incoordination associated with gait alterations with frequent falls. The recent detection, two weeks before the consultation date of a scrotal skin lesion, 4x2cm in diameter and 2cm thick, of elastic consistency, painless, ulcerated, compatible with syphilitic gum, stands out. On suspicion of tertiary syphilis, he was referred to the emergency service, with subsequent admission and confirmation of neurosyphilis, having followed prolonged therapy with intravenous penicillin, with an improvement of the neurological condition. Three months later, he was re-hospitalized for reactivation neurosyphilis and medicated with penicillin, followed, after discharge, by a worsening of his clinical condition, with cachexia, a global decrease of muscle strength more evident in the lower limbs, marked dysarthria, and progressive dysphagia. He died 11 months later from healthcare-associated pneumonia. Comment: In this clinical case, the presence of a potentially reversible cause of dementia stands out: neurosyphilis. After treatment, there was a partial improvement of the clinical condition, however without complete recovery and with subsequent progressive deterioration. This aspect is justified by the late diagnosis and by the concomitant presence of other etiological factors for dementia syndrome. By knowing the personal antecedents, the socio-familiar context, and the patient's previous condition, the family doctor is in a privileged position for the early diagnosis and orientation of these situations.